Pewarnaan Pelangi Antiajaib pada Amalgamasi Graf - Riniatul Nur Wahidah; Dafik Dafik; Ermita Rizki Albirri (jcgant, 2022)
Let G is a connected graph with vertex set V(G) and edge set E(G). The side weights for uvE(G) bijective function f:V(G)→{1,2,…, |V(G)|} and w(uv)= f(u)+f(v) . If each edge has a different weight, the function f is called an antimagic edge point labeling. Is said to be a rainbow path, if a path P on the graph labeled vertex G with every two edges ,u'v'E(P) fulfill w(uv)≠ w(u'v') . If for every two vertices u,v V(G), their path uv rainbow, f is called the rainbow antimagic labeling of the graph G. Graph G is an antimagic coloring of the rainbow if we for each edge uv weight color side w(uv). The smallest number of colors induced from all sides is the rainbow antimagic connection number G, denoted by rac(G). This study shows the results of the rainbow antimagic connection number from amalgamation graph.